The Transformative Impact of Artificial Intelligence on Economics - Silmi, Tsabita Atina (Advances in Global Economics and Business Journal, 2024)
The swift progress in artificial intelligence (AI) is expected to have a profound impact on the global economy. This document systematically reviews the economic implications of AI, placing a central emphasis on improving productivity and fostering economic growth. It explores the consequences of AI on employment and examines whether it will contribute to the widening of income inequality. In consideration of these aspects, a summary is provided regarding the implementation of public policies designed to alleviate potential negative effects of AI on employment structures and income distribution. Lastly, the paper concludes with a brief overview and delineates potential areas for future research. The insights from this study are essential for formulating effective policy strategies to navigate the societal and economic consequences of AI. In summary, the world must be ready to confront both the challenges and opportunities arising from the rapid advancements in the field of AI to maximize benefits and minimize risks